BIOM-18. METHYLATION ANALYSIS TO REVEAL THE CELLULAR ORIGIN OF PROGNOSTIC CIRCULATING CELL-FREE DNA IN GLIOBLASTOMA. (12th November 2021) - Till, Jacob; Abdalla, Aseel; Wang, Zhuoyang; Zhou, Wanding; Nabavizadeh, S Ali; Binder, Zev; Hussain, Jasmin; Black, Taylor; Yee, Stephanie; Desai, Arati; Bagley, Stephen J; Carpenter, Erica
Abstract: We have previously demonstrated an independent association between high levels of plasma circulating cell-free DNA (ccfDNA) concentration and poor survival outcomes in patients with newly diagnosed glioblastoma. Given that somatic mutations are rarely detected in glioblastoma patient plasma, we reasoned that DNA shed by tumor (circulating tumor DNA, ctDNA) was not likely to be a driver of prognostic increases in ccfDNA. To investigate the tissue of origin for this prognostic ccfDNA, we analyzed the plasma ccfDNA methylation signatures of 23 patients with newly diagnosed glioblastoma using the Illumina Infinium EPIC array, a genome-wide DNA methylation technique covering over 850, 000 CpG sites. Deconvolution of the ccfDNA methylation signatures based on published reference methylomes revealed an increased proportion of ccfDNA derived from granulocytes in glioblastoma specimens compared to healthy controls (p < 0.0001). Further, this granulocyte proportion was increased in patients with high ccfDNA levels (above median value) compared to patients with low ccfDNA (p = 0.0001). Granulocyte proportion correlated with ccfDNA concentration (Spearman r = 0.64, p = 0.001). The top two gene sets identified by differential methylation analysis followed by gene set enrichment analysis (methylGSA) between high- and low-ccfDNA specimens were "neutrophil activation involved in immune response" (GO:0002283, p = 3.4E-23) and "neutrophil degranulation" (GO:0043312, p = 3.4E-23). Additional analysis of ccfDNA fragment size identified larger fragments ( > 700 bp) as the major source of the prognostic signal (log-rank p = 0.002 for progression-free survival) compared to traditionally sized ccfDNA fragments (50-700 bp, log-rank p = 0.12). Taken together, these data suggest that granulocytes are the primary contributing source of prognostic ccfDNA in glioblastoma. Future studies are needed to determine the mechanism through which granulocyte-derived ccfDNA is associated with clinical outcomes in glioblastoma and to explore related therapeutic opportunities.